THE EFFECT OF PQ4R ON STUDENTS' READING COMPREHENSION AT THE EIGHT GRADE STUDENTS OF MADRASAH TSANAWIYAH NEGERI 1 JAMBI - Abd Muiz, Mesy Ulvianti (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2023)
The objectives of this study was to find out whether any significant effect between before and after giving treatment in the experimental class. This research used quasi experimental design with pretest posttest control class design, while the research instrument is the form of giving multiple choice tests. The sample was taken from the eighth grade students of Madrasah Tsanawiyah Negeri 1 Kota Jambi. The experimental class was taught by using Preview, Question, Read, Reflect, Recite, Review (PQ4R) Strategy, Meanwhile the control class was taught without using Preview, Question, Read, Reflect, Recite, Review (PQ4R) Strategy. Before giving the treatment, the students from both the classes were given a pretest to know their ability in reading comprehension. At the end of the treatment, the students were given a posttest. The tests used as instrument were consisting of 30 multiple choice questions. The final mean scores gained from both classes was analyzed by using t-test with significance level α = 0,05 by using the pooled variance mode t-test, it was found that the mean score of experimental class was 80,13 meanwhile, the control class was 70,53. The result related that was significant was determined by < 0,05, = 0,000. Thus, H1 was accepted that Preview, Question, Read, Reflect, Recite, Review (PQ4R) Strategy can bring significant effect to the eighth grade students’ reading comprehension at the eighth grade students of Madrasah Tsanawiyah Negeri 1 Kota Jambi.